Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
x=6 , y = 4
Step-by-step explanation:
( x-2,6)=(4,Y+2)
this means; (x-2) &( 4) stands for" x "axis.
and( 6 )& (y+2) stands for y axis.
So, we can say( x-2)=X1 & (4)=X2 , (6)=Y1 & (y+2)=Y2
then; to Solve The Equation we use The Formula: X1=X2 for "X" And Y1=Y2 for "Y".
Solution: for "X" ; X1=X2
x-2= 4
x=4+2
x=6
For "Y" ; Y1=Y2
6 = y+2
y=6-2
y=4
finally check ; ( (x-2),6) = (4,(y+2) )
(6-2),6 = (4,(4+2) )
( (4),6) = (4,(6) )
(4,6) = (4,6)
so, X1 =X2 ; 4 = 4
Y1 = Y2 ; 6 = 6
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.